Conditional Cash Transfer Program and Leprosy Incidence: Analysis of 12.9 Million Families From the 100 Million Brazilian Cohort. Issue 12 (8th July 2020) - Pescarini, Julia M; Williamson, Elizabeth; Ichihara, Maria Y; Fiaccone, Rosemeire L; Forastiere, Laura; Ramond, Anna; Nery, Joilda Silva; Penna, Maria Lucia F; Strina, Agostino; Reis, Sandra; Smeeth, Liam; Rodrigues, Laura C; et al.
Abstract: Leprosy is a neglected tropical disease predominately affecting poor and marginalized populations. To test the hypothesis that poverty-alleviating policies might be associated with reduced leprosy incidence, we evaluated the association between the Brazilian Bolsa Familia (BFP) conditional cash transfer program and new leprosy case detection using linked records from 12, 949, 730 families in the 100 Million Brazilian Cohort (2007–2014). After propensity score matching BFP beneficiary to nonbeneficiary families, we used Mantel-Haenszel tests and Poisson regressions to estimate incidence rate ratios for new leprosy case detection and secondary endpoints related to operational classification and leprosy-associated disabilities at diagnosis. Overall, cumulative leprosy incidence was 17.4/100, 000 person-years at risk (95% CI: 17.1, 17.7) and markedly higher in "priority" (high-burden) versus "nonpriority" (low-burden) municipalities (22.8/100, 000 person-years at risk, 95% confidence interval (CI): 22.2, 23.3, compared with 14.3/100, 000 person-years at risk, 95% CI: 14.0, 14.7). After matching, BFP participation was not associated with leprosy incidence overall (incidence rate ratio (IRR)Poisson = 0.97, 95% CI: 0.90, 1.04) but was associated with lower leprosy incidence when restricted to families living in high-burden municipalities (IRRPoisson = 0.86, 95% CI: 0.77, 0.96). In high-burden municipalities, the association was particularly pronounced for paucibacillary cases (IRRPoisson = 0.82, 95% CI: 0.68, 0.98) and cases with leprosy-associated disabilities (IRRPoisson = 0.79, 95% CI: 0.65, 0.97). These findings provide policy-relevant evidence that social policies might contribute to ongoing leprosy control efforts in high-burden communities.